(untitled) (Raparin Journal of Humanities (RJH), 2023)
The act has of Persuasion has existed since ancient times. At every stage of life, People have tried to Persuade others in various techniques and methods .This process, has covered all areas of life and continues. The producer of discourse requires technique, expertise and skill to convince the other person. Of course, this is done through language, so during the outbreak of the coronavirus, speakers were trying to convince people to follow convince people to follow the health guidelines. Because health discourse is directly related to the life of every individual in society, it is duty of the government and authorities to protect society and prevent the spread of any disease. Therefore, during the outbreak of this global epidemic around the world and Kurdistan, especially the discourses were devoted to the health and prevention of citizens. Because if health discourse is controlled by scientific opinion, it is in terms of social reality and the types of choices of methods and descriptions by which the virus is known, It is not controlled by the speakers, because each uses a persuasive method to convey his intention.